Sustainable Planning And Development Of Smart City - Aji, Gumiwang Restu; Salahudin, Salahudin (Journal of Social Studies Arts and Humanities (JSSAH), 2024)
This study aims to provide a comprehensive understanding of sustainable planning and development strategies for smart cities by conducting a systematic literature review of research published in reputable international journals. The analysis was carried out using the Scopus database, focusing on studies published in 2020 that examined the relationship between urban planning, sustainable development, and smart city implementation. A total of 270 relevant articles were identified and analyzed using bibliometric techniques with the VOSviewer software to map keyword networks, thematic clusters, and research trends. The findings reveal four dominant thematic clusters: (1) governance and implementation challenges in smart city planning, (2) infrastructure and digital services, (3) sustainability frameworks and policy objectives, and (4) information systems and citizen engagement. The study highlights that sustainable smart city planning requires integration across governance, technology, environment, and social participation dimensions. Moreover, the research indicates that effective planning and development depend on adaptive policies, data-driven decision-making, and multi-stakeholder collaboration. Despite significant progress, disparities in technological infrastructure and governance capacity remain critical challenges, particularly in developing countries. This paper contributes to the conceptual and methodological advancement of smart city research by mapping global knowledge trends and proposing future research directions for sustainable urban development.